Keabsahan Akta Notaris terkait Risalah Rapat Umum Pemegang Saham Perseroan Terbatas yang Dilakukan Secara Online - I Made Pradnyana Utama (CV Rewang Rencang, 2025)
This article was written with the aim of reviewing and analyzing the validity of notarial deeds related to minutes of general meetings of shareholders of limited liability companies conducted online. The research method used is normative legal research because the focus of the study is based on the conflict of norms between